ACT-3 Reactor-based boron neutron capture therapy with add-on bevacizumab for recurrent malignant glioma: The final report. (6th December 2021) - Furuse, Motomasa; Kawabata, Shinji; Wanibuchi, Masahiko; Shiba, Hiroyuki; Takeuchi, Koji; Kondo, Natsuko; Tanaka, Hiroki; Sakurai, Yoshinori; Suzuki, Minoru; Ono, Koji; Miyatake, Shin-Ichi
Abstract: Background: Re-irradiation had a higher rate of radiation injury because recurrent MG had already irradiated in the first-line treatment. Recently, combination therapy of re-irradiation and bevacizumab showed a lower incidence of radiation injury than re-irradiation alone. Boron neutron capture therapy (BNCT), a tumor-selective particle radiation therapy, also increased radiation injury for recurrent MG, despite the greater focus on tumor cells. In this study, we evaluated the efficacy of BNCT plus bevacizumab with early induction after BNCT. Methods: Patients with recurrent MG were prospectively enrolled in this study. BNCT was performed using Kyoto University Research Reactor as a neutron source. Bevacizumab of 10 mg/kg was initiated 1–4 weeks after BNCT and was continued every 2–3 weeks until disease progression. Newly-diagnosed (de novo) glioblastoma was categorized as primary GBM (pGBM). Other MG were categorized as non-pGBM. Results: Kyoto University Research Reactor stopped irradiation for clinical use in February 2019. Twenty-five patients (14 pGBM and 11 non-pGBM) were treated with this combination therapy between June 2013 and February 2019. The median Overall survival (OS) after BNCT was 21.4 months for pGBM and 73.6 months for non-pGBM, respectively (p = 0.0428). The median progression-free survival (PFS) after BNCT was 8.3 months for pGBM and 15.6 months for non-pGBM, respectively (p = 0.0207). The objective response rate was 72 %. Alopecia occurred in all patients. Adverse events ≥ grade 3 were grade 3 proteinuria in four patients, grade 5 myocardial infarction in one patient, and grade 5 meningitis in one patient. Conclusion: BNCT plus bevacizumab showed a long OS and a long PFS, compared to our previous studies of BNCT alone for recurrent MG. Bevacizumab could provide beneficial effects not only for tumor itself, but also radiation injury. Further research with a larger sample using accelerator-based BNCT and bevacizumab is required to elucidate the efficacy and safety of this combination therapy.